Algorithm for foggy image enhancement based on the total variational Retinex and gradient domain - Bing-quan CHEN; Hong-li LIU (Tongxin xuebao)
Considering the preservation of color constancy and the improvement of contrast ratio of foggy image en-hancement, the foggy image enhancement algorithm based on the total variational Retinex gradient domain method was proposed. Firstly, the algorithm used the GS（Gauss-Seidel）iterative method to resolve the Retinex variational energy functional so that the color constancy was remained and the operational velocity of the proposed algorithm was improved. Secondly, the algorithm stretched strongly the gradient of the higher light blocks in the foggy image by combining the relative gradient and the absolute gradient, and reconstructed the foggy enhancement images with the context of least squares and extended the enhancement method to process the color images. Lastly, the enhancement images by using the total variational Retinex method and the gradient domain algorithm were fused weightedly to keep the color constancy and improve the contrast ratio. The experimental results show that the proposed algorithm can effectively improve the image's contrast and definition,the algorithm could keep better color constancy and high color fidelity.